Experimental Investigation on Thermal Efficiency of a Solar Collector with Helical Coil Tube using MWCNT/WATER - et. al., Dr.K. Palanisamy, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The thermodynamic energy conversion efficiency collector was experimentally studied in this investigation with helical coil tube using MWCNT (Multi Walled Carbon Nano Tube). The collector is made up of a curved glass tube with a helical coil as the solar power receiver. Also, these efficiencies with MWCNT nano fluid far from isoelectric points higher than other nano fluid. The MWCNT/water nano fluids were prepared in two steps with the addition of surfactant at particle volume concentrations of 0.1, 0.3, and 0.5 percent. The prepared MWCNT/water nano fluids are found to be safe even after 4 weeks of preparation, with no considerable deposit of nano ducts on the tube interior layer. There no immediate risk in dealing with MWCNT and it is being studied and inspected MWCNT exhibits no extreme threat, and it is being studied and thoroughly checked. Therefore, MWCNT / water nano fluids transfer heat transfer fluids with a significant pressure drop to conventional fluids in a helical, enhance heat transfer, use a coiled tube heat exchanger. Adequate performance of elevated materials Chemical, petroleum, temperature is a potential issue in many systems process and power generation industries. Decomposition of materials is caused by the interaction between the structural material and the exposure environment.